Impact of Mining on River Water Quality in Roșia Montană Area, Romania, and the Use of Zeolites for Acid Mine Drainage Remediation - Mirel Glevitzky; Roxana Bostan; Simona Varvara; Mihai-Teopent Corcheş; Gabriela-Alina Dumitrel; Maria Popa (Clean Technologies, 2025)
Mining activities have a significant impact on the quality of river water in the Roșia Montană area. This region, known for its gold and other precious metal mining, serves as an example of the interaction between anthropogenic activities and the natural environment. Water from mine drainage is metal-rich and contaminates the environment, inhibiting the growth and reproduction of aquatic plants and animals, while also having corrosive effects on infrastructure. As part of the study, parameters such as pH, dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, sulfates, and heavy metals were monitored for the rivers in the area (Roșia Montană, Săliște, Corna, Abrud, and Arieș). Roșia Montană river shows a decrease in pH to highly acidic values (2.69–3.95), especially in the downstream sections. Sulfate concentrations exceed 3600 mg/L, and heavy metal concentrations (Fe, Zn, As, Mn) increase significantly, indicating severe pollution, primarily originating from the Gura Mine gallery. These frequently exceed the thresholds corresponding to water quality classes I and II, and in some cases even surpass the limits of class V (the most polluted). The presence of As (27.60 µg/L) in Roșia Montană River indicates a significant ecotoxicological risk. In an attempt to treat the acid mine drainage from Roșia Montană, a natural zeolite was used at different doses. The results obtained show good efficiency of zeolite in removing the metal ions (Fe, Zn, and Mn). The results provide valuable information on the quality of river waters in the mining area of Roșia Montană and suggest that zeolite can be used effectively to decontaminate mine waters.